PENERAPAN PEMBELAJARAN MODEL SIKLUS BELAJAR PADA MATERI JAMUR DI SMA - Wulandari, Barkah; Kartijono, Nugroho Edi; HB, F. Putut Martin (Journal of Biology Education, 2013)
This research was aimed to identify the activities and studentsâ learning outcomes at SMA Negeri 1 Klirong on the fungi materials in learning cycle model. Learning cycle model was optimize if in the learning process, the studentsâ activities showed that â¥ 75% of students are active and very active, with studentsâ learning outcomes reached to score â¥ 80. This research was conducted at SMA Negeri 1 Klirong in class X.6 and X.7. Sample was taken by purposive sampling technique in one shot case study design.The data of this research consists of main and supporting data. The main data consists of the studentsâ activities by observation and the studentsâ learning outcomes were obtainedÂ  fromÂ  assignment, report, andÂ  final test, while the supporting data consists of teacherâs perfomance by observation, teacherâs and studentsâ responses were collected by questionnaires. The results of this research showed that activities of all students in class X.6 dan X.7 are active and very active, with the studentsâ learning outcomes reached to score > 80. The conclusion was the application of learning cycle model can optimize of activities and studentsâ learning outcomes of SMA Negeri 1 Klirong on the fungi materials.Â Penelitian ini bertujuan untuk mengetahui aktivitas dan hasil belajar siswa SMA Negeri 1 Klirong pada materi jamur dalam pembelajaran model siklus belajar. Pembelajaran model siklus belajar dikatakan optimal apabila aktivitas siswa dalam proses pembelajaran menunjukkanÂ  â¥ 75% siswa aktif dan sangat aktif, dengan hasil belajar mencapai â¥ 80. Penelitian ini dilakukan di SMA Negeri 1 Klirong pada kelas X.6 dan X.7. Pengambilan sampel dilakukan dengan teknik purposive sampling dengan desain penelitian one shot case study. Data dalam penelitian ini terdiri dari data utama dan data pendukung. Data utama terdiri dari data aktivitas siswa yang diperoleh dari lembar observasi dan hasil belajar siswa yang diperoleh dari nilai tugas, laporan, dan tes evaluasi akhir, sedangkan data pendukung terdiri dari kinerja guru yang diperoleh dari lembar observasi serta tanggapan siswa dan guru yang diperoleh dari lembar angket. Hasil penelitian menunjukkan bahwa aktivitas seluruh siswa kelas X.6 dan X.7 mencapai kriteria aktif dan sangat aktif, dengan hasil belajar siswa mencapai skor > 80. Disimpulkan bahwa, pembelajaran model siklus belajar dapat mengoptimalkan aktivitas dan hasil belajar siswa SMA Negeri 1 Klirong pada materi jamur..